Ecotourism development based on local community empowerment: A case study in the forest village community institution of Wana Cendana, Dago Village, Bogor Regency - Ligar Abdillah; Dody Prayogo (Universitas Trunojoyo Madura, 2020)
Forest Village Community Institutions (Lembaga Masyarakat Desa Hutan) generally use forest in the agriculture sector in accordance with instructions and capital support from Perhutani. LMDH Wana Cendana operates in the ecotourism sector without instructions and capital assistance from Perhutani. This study aims to analyze the implementation of empowering local communities (LMDH Wana Cendana) who do not have expertise in the field of forest management and ecotourism. The concept used is the empowerment of local communities and ecotourism with qualitative case study methods, thus promoting the novelty of cases and in-depth interviews with informants who are directly involved in the development of Gunung Dago ecotourism. Some previous research shows that empowerment does not prioritize local communities. The development of ecotourism in Dago Village, which began in 2019, prioritizes local potential and independent learning processes, so that local communities are able to transform ex-mining land into beautiful tourist attractions. The independence of the local community is reflected in its involvement in the ecotourism development process, from planning to implementation. In addition, local communities as managers are able to utilize local knowledge, culture and resources to improve the welfare of members without overruling the rules of forest conservation.